2022
DOI: 10.1177/01926365221123924
|View full text |Cite
|
Sign up to set email alerts
|

Latinx High School Students' Perceptions About Their High School Experiences

Abstract: Does student voice matter? This study examined how Latinx students used their voice to share their experiences about how they were perceived and treated at their schools. Data collection included focus groups with Latinx students. Students’ responses indicated they did not feel safe nor did their school create a caring environment. Students’ also noted their concerns about not getting access to school counselors or post-secondary schooling. Findings indicated that listening to students is an important factor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Much to our chagrin, this was the first opportunity for these students to provide their opinions and perspectives. The students who participated provided an overall perspective of their personal experiences and treatment from administrators and teachers at their respective campuses [21].…”
Section: Students' Perceptions Of School Inclusivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Much to our chagrin, this was the first opportunity for these students to provide their opinions and perspectives. The students who participated provided an overall perspective of their personal experiences and treatment from administrators and teachers at their respective campuses [21].…”
Section: Students' Perceptions Of School Inclusivenessmentioning
confidence: 99%
“…This study revealed the importance of listening to students and responding to their concerns. Findings indicated schools are often unwilling to collaborate and coordinate with students [21]. This approach is particularly important in populations with high mobility and high percentages of low socioeconomic populations.…”
Section: Students' Perceptions Of School Inclusivenessmentioning
confidence: 99%
See 1 more Smart Citation